PENGUKURAN KUALITAS HIDUP PASIEN TUBERKULOSIS MENGGUNAKAN INSTRUMEN ST GEORGE RESPIRATORY QUESTIONNAIRE (SGRQ) DI YOGYAKARTA - Hendrik Hendrik; Dyah Aryani Perwitasari; Ully Adhie Mulyani; Jarir At Thobari (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Tuberculosis (TB) is an infectious disease caused by the bacillus Mycobacterium tuberculosis. It typically affects the lungs but can affect other sites as well. TB disease could influence the TB patients’ quality of life such as psychology of health, physical function and the leading role in society. The purpose of this research is to measure the differed TB patients’ quality of life before and during the treatment using Indonesian version of St George Respiratory Questionnaire (SGRQ) instruments that have been validated. The research used a cross-sectional design conducted prospectively in 91 new patients diagnosed as lung TB in BP4 province of Yogyakarta in November 2013 until April 2015. Patients filled out the questionnaires, and its obtained Total Score values were analyzed with Friedman's test to understand the quality of life. The results from this research showed that the quality of life of TB patient before, and during the treatment differed significantly. The Total score on the first month treatment was 43.57% and the second until the sixth months treatment was 30.40%; 25.22%; 20.50%; 18.45% and 16.51% respectively (p<0.05). The worst of quality of life was occurred in the first month treatment as the initial period before the treatment and continues to improve until the sixth-month treatment. In conclusion, the quality of life TB patients’ before and during the treatment is more increasing. Key words: Tuberculosis, SGRQ, Quality of life.